Microstructural and textural evolutions in multilayered Ti/Cu composites processed by accumulative roll bonding. Issue 6 (June 2019) - Jiang, Shuang; Peng, Ru Lin; Jia, Nan; Zhao, Xiang; Zuo, Liang
Graphical abstract: Highlights: Grain refinement in Ti is induced by dynamic recrystallization and large deformation. Significant grain refinement in Cu is only observed in shear banded region. Nano-scaled amorphization appears at interfaces even after one roll bonding pass. Amorphous region widens with further bonding and compounds appear from the region. Abnormal 11 2 ¯ 0 fiber texture evolves in Ti, while brass-type textures evolve in Cu. Abstract: Ti/Cu multilayered composites were fabricated via accumulative roll bonding (ARB). During co-deformation of the constituent metals, the hard Ti layers necked preferentially and then fragmented with the development of shear bands. Transmission electron microscopy showed that with increasing ARB cycles, grains in Ti were significantly refined even though dynamic recrystallization has occurred. For Cu the significant grain refinement was only found within the shear banded region when the composite was processed after five ARB cycles. Due to the diffusion of Cu atoms into Ti at the heterophase interfaces, amorphization with a width less than 10 nm was identified even in the composite processed by one cycle. At higher ARB cycles, the width of amorphous region increased and intermetallic compounds CuTi appeared from the region. The lattice defects introduced at the heterophase interfaces under roll bonding was responsible for the formation of the nano-scaled compounds. X-ray diffraction showed that an abnormal 11 2 ¯ 0 fiber texture was developed in Ti layers, while significant brass-type textures were developed in Cu layers. Some orientations along the 11 2 ¯ 0 fiber favored the prismatic < a> slip for Ti. Tensile tests revealed the elevated strength without a substantial sacrifice of ductility in the composites during ARB. The unique mechanical properties were attributed to the significantly refined grains in individual metals, the good bonding between the constituent metals, as well as the development of an abnormal 11 2 ¯ 0 fiber texture in Ti layers.